An empirical investigation of campus portal usage - Saghapour, Mohsen; Iranmanesh, Mohammad; Zailani, Suhaiza; Goh, Gerald Guan Gan (Springer, 2018)
This study has determined the determinants of the perceived ease of use and perceived usefulness and their influence on campus portal usage. A quantitative approach was employed, using a five-point Likert scale questionnaire, adapted from previous studies. Data were gathered through a survey conducted with 341 staff working in the University of Malaya and were analysed using the partial least squares technique. The results indicate that the ease of finding and ease of understanding have a positive impact on the perceived ease of use of the campus portal. Furthermore, this study also reported a significant positive effect of service quality, information, and process on perceived usefulness of the campus portal. Our study suggests that the perceived ease of use and usefulness are vital towards enhancing the usage frequency and volume of the campus portal. This study broadens the knowledge concerning factors that increase campus portal usage which will enable academic institutions to refine the campus portal thus enhancing the portal usage.